MYC regulates ribosome biogenesis and mitochondrial gene expression programs through its interaction with host cell factor–1 - Tessa M Popay; Jing Wang; Clare M Adams; Gregory Caleb Howard; Simona G Codreanu; Stacy D Sherrod; John A McLean; Lance R Thomas; Shelly L Lorey; Yuichi J Machida; April M Weissmiller; Christine M Eischen; et al. (eLife, 2021)
The oncoprotein transcription factor MYC is a major driver of malignancy and a highly validated but challenging target for the development of anticancer therapies. Novel strategies to inhibit MYC may come from understanding the co-factors it uses to drive pro-tumorigenic gene expression programs, providing their role in MYC activity is understood. Here we interrogate how one MYC co-factor, host cell factor (HCF)–1, contributes to MYC activity in a human Burkitt lymphoma setting. We identify genes connected to mitochondrial function and ribosome biogenesis as direct MYC/HCF-1 targets and demonstrate how modulation of the MYC–HCF-1 interaction influences cell growth, metabolite profiles, global gene expression patterns, and tumor growth in vivo. This work defines HCF-1 as a critical MYC co-factor, places the MYC–HCF-1 interaction in biological context, and highlights HCF-1 as a focal point for development of novel anti-MYC therapies.